Objectively measuring social attention of thyroid neck scars and transoral surgery using eye tracking. (22nd March 2019) - Juarez, Michelle C.; Ishii, Lisa; Nellis, Jason C.; Bater, Kristin; Huynh, Pauline P.; Fung, Nicholas; Darrach, Halley; Russell, Jonathon O.; Ishii, Masaru
Abstract : Objective: Measure the social attention of thyroid neck scars and transoral surgery using eye tracking. Methods: Observers viewed images of patients with thyroid neck scars, control patients with no scars, and patients who underwent transoral thyroidectomy as an eye‐tracking monitor recorded their eye movements. Hotelling's multivariate analysis, followed by planned posthypothesis testing, were used to compare fixation times for the central triangle (CT), peripheral face, and neck between the three groups. To assess if these gaze patterns would normalize with transoral surgery, a two‐sample t test was done to assess for differences in neck fixations between control and transoral patients and between transoral and traditional thyroidectomy. Results: One hundred and thirty participants completed the eye‐tracking experiment (mean age 24.3 years, 65 females). Observers directed the majority of their attention to the CT in both control and scar patients. Observers paid more attention to the neck (103.72 ms, P  < .0001, 95% confidence interval [CI] [55, 152] ms) and less to the peripheral face (115.50 ms, P  = .01, 95% CI [19, 211] ms) in patients with neck scars than in control patients. Furthermore, transoral surgery eliminated this attentional distraction wherein there was no difference in the fixation time to the neck (−39.198 ms P  = .16, 95% CI [−93.978, 15.5816] ms) between controls and those who underwent transoral surgery. Conclusion: Observers directed their gaze away from the face and toward the neck in patients with thyroid neck scars. Furthermore, this distraction was eliminated with tranoral surgery. These findings shed light onto the altered observer perceptions of patients with thyroid neck scars. Level of Evidence: NA Laryngoscope, 129:2789–2794, 2019